(Effective communication skill among students of psychological counseling and educational guidance departments in the faculties of basic education) (build and apply) (Journal of the College of Basic Education, 2022)
The subject of effective communication skill occupies an important space in the thinking of human societies because it is an important dynamic human activity through which information, ideas and experiences are transferred, no matter how large or small, from one individual and from one group to another. So far, and in this way, the process of effective communication is an urgent necessity in human society, but we find that there is a disparity between individuals in this process, as we find that there is a category of individuals who have effective communication in society, and besides that, a group that hinders effective communication or lacks effective communication.Search objective:1- Building an effective communication skill scale for female students of the psychological counseling and educational guidance departments in the faculties of basic education.2- Recognizing the effective communication skill among students of the psychological counseling and educational guidance departments in the faculties of basic education. The researcher built an effective communication skill scale consisting of (30) items in a five-graded declarative style, extracting the psychometric properties of honesty (discriminatory strength, internal homogeneity and stability by re-test method, (Alpha-Cronbach) equation and the statistical indicators of the scale, and verifying the second objective using T-test for one sample.The research reached the following results:It was found that the students of the stage of psychological counseling and educational guidance departments have the effective communication skill in an average manner by knowing the calculated T value after comparing it with the tabular T value when applying the effective communication skill scale on the diagnostic sample.The environment surrounding the students has a clear impact on learning the skill of effective communication alike, and such programs help to teach them and develop positive ideas and behaviors through interaction with the activities provided through the counseling sessions and this helped them to learn remarkably.To complement the current research, the researcher presented a number of recommendations and suggestions.